Behavioral and neural correlates of social network size: The unique and common contributions of face recognition and extraversion. Issue 2 (2nd September 2021) - Wang, Xu; Zhen, Zonglei; Xu, Shan; Li, Jingguang; Song, Yiying; Liu, Jia
Abstract: Objectives: Humans are inherently social creatures and can gain advantages from larger network size. Researches have shown that different cognitive and personality factors may result in individual differences of social network size (SNS). Here, we focused on whether face recognition ability and extraversion were related to SNS and the neural basis underlying the relations. Methods: Behaviorally, we adopted the face‐inversion task, NEO personality inventory, and computerized SNS test to explore the relationships between face recognition, extraversion, and SNS. Neurally, we used resting state functional magnetic resonance imaging and fractional amplitude of low‐frequency fluctuation (fALFF) analysis method to investigate the neural correlates of SNS and then revealed whether face recognition and extraversion were related to SNS relevant brain regions. Results: We found that individuals with better face recognition ability and more extraverted personality had larger size of social network. In addition, we found that SNS was positively associated with the fALFF in the ventromedial prefrontal cortex (vmPFC), right superior temporal sulcus, and precuneus. Interestingly, the fALFF in the vmPFC significantly correlated with face recognition ability. Conclusions: Our study suggests that both face recognition and extraversion may be important correlates of SNS, and the underlying spontaneous neural substrates are partially dissociable.